PENGEMBANGAN BISNIS TANPA RIBA - Iwan Setiawan (TAHKIM, 2017)
The development of wealth is not something that is prohibited but God has outlined the rules in the development of wealth to create harmony and human order. The development of assets with usury instruments is a prohibited method. Likewise with interest based on the 2003 MUI fatwa which states that even interest is usury that is unlawful. Usury is not only forbidden based on the syar'i argument, but the practice of usury has a negative impact on the economic order of a country. This study uses a descriptive qualitative research approach, namely by describing the phenomenon of usury as well as arguments that are pro and counter to interest as an innovation of capitalist ideology. The results of this study are that interest included in usury is prohibited even though it does not multiply and has a negative impact on the economy such as causing inflation in 1998. The solution to avoiding usury practices is the mudharabah contract. This contract is friendly to entrepreneurs and consumers because profits and losses are borne together. Keywords: Usury, business, interest